Exploring the implementation of relational practice in a primary school to support school attendance - Alaimo, George; Kelly, Catherine (Frontiers in Education, 2025)
School attendance difficulties are increasingly recognised as complex challenges, rooted in emotional, relational, and systemic influences. This study explores how relational practice can be implemented in a primary school to support attendance, using the term School Attendance Barriers to avoid deficit-based language and emphasise systemic drivers. The study examined school staff perceptions of the key factors influencing the implementation of relational practice. A qualitative action research design was used, underpinned by critical realism and conducted over one academic year in a primary school in Northwest England. Seven staff members, including senior leaders, teachers, and teaching assistants, formed a collaborative research group. Data were gathered from four recorded meetings, transcribed and analysed using inductive qualitative content analysis. Findings identified key facilitators, including strong leadership buy-in, a shared relational ethos, and psychological input to support reflective practice. The co-developed implementation of Emotion Coaching was particularly valued for offering a feasible, relational way of being. Barriers included curriculum pressures, staffing inconsistencies, limited training, and tensions between relational approaches and wider educational policies. The study highlights the value of participatory approaches, such as action research, in embedding sustainable, school-owned relational practice. It challenges prescriptive models of social and emotional learning, calling instead for flexible, context-sensitive implementation tailored to staff experience and school systems.